The scope of permissible indirect immissions in neighbourhood relations in the light of the supreme court's jurisprudence, common and administrative courts: outline of the issue - Krawczyk, Michał (Management and Administration Journal, 2019)
According to the code regulation, the owner of the property, while exercising his rights, should refrain from activities that would disrupt the use of properties in the neighourhood beyond the average measure that comes from the socio-economic destination of real estate and local relations. Reasons determining the admissibility or inadmissibility of certain indirect immissions are presented in the form of general clauses. The proper interpretation of the issue can be made only on the basis of the analysis of the rich court jurisprudence in this matter. The art. 144 of civil code regulates the subject, both material and immaterial immunities that influence the psychic sphere of the neighbourhood property owner. However, the mere fact of occurrence of immission is not sufficient to claim protection under art. 144 civil code. It is also necessary that the immission should exceed the average measure resulting from the socio-economic destination of real estate and local relations. The assessment of the average measurement should be made on the basis of objective conditions and not on the basis of subjective feelings of the property owners. It should take into account, among others the purpose of both properties, frequency of disturbances, their time and intensity. In the case of occurrence of the immission referred to in 144 k.c., the owner of the neighbouring property has the right to prohibit the immission and restore the lawful state. In practice, there is the possibility of overlapping of a claim under art. 144 civil code with a compensation claim based on art. 415 civil code or a claim for the protection of personal rights according to art. 24 civil code. In the first case, the demand to stop the immission does not exclude the simultaneous seeking of appropriate compensation. In the second case, the injured party is entitled to choose the right request.